Selling ‘hot air’: An Analysis of the Perceived Media Influence on Prosperity Gospel Related Gullibility in Zimbabwe - Gadzikwa, Wellington (Alternation - Interdisciplinary Journal for the Study of the Arts and Humanities in Southern Africa, 2020)
The close to three-decade economic and political crisis in Zimbabwe, or what is commonly known as the ‘Zimbabwean Crisis’ (Raftopoulos 2009) has brought desperation to many Zimbabweans. In almost every facet of life the church has become a form of refuge. What has baffled many observers is the manner in which the populace has imbibed the Prosperity Gospel and its promises in a land that resembles a desert. The mushrooming of Prosperity Gospel churches in Zimbabwe, in which only the leaders of these churches have prospered materially, while congregants continued to live on faith and hope, demonstrates among other things how gullible our society has become. Through an analysis of selected print media articles on Prosperity Gospel in mainstream newspapers in Zimbabwe and structured key informant interviews, this article argues that the media, through mass manipulation, have to a large extent aided and entrenched religious gullibility in unprecedented ways even among the elite.
free